Numerical Analysis of Bioinspired Tails in a Fixed-Wing Micro Air Vehicle - Estela Barroso Barderas; Rafael Bardera Mora; Ángel Antonio Rodriguez-Sevillano; Juan Carlos Matías García (Aerospace, 2023)
Bird tails play a key role in aerodynamics and flight stability. They produce extra lift for takeoff and landing maneuvers, enhance wing functions and maintain stability during flight (keeping the bird from yawing, rolling and pitching, or otherwise losing control). This paper investigates the use of bioinspired horizontal stabilizers for Micro Air Vehicles (MAVs) involving a Zimmerman wing-body geometry. A selection of five tail shapes of the main types existing in nature is presented, and a parametric analysis is conducted looking into the influence of the most relevant tail geometric parameters to increase the longitudinal static stability of the vehicle. Based on the parametric study, a smaller subset of candidate tail designs are shortlisted to perform a detailed aerodynamic analysis. Then, steady RANS CFD simulations are conducted for a higher-fidelity study of these candidate tail designs to obtain an optimum of each tail type. The criterion for selection of the optimum tail configuration is the maximum aerodynamic efficiency, <semantics>CLCD<mtext> </mtext></semantics>, as well as a high longitudinal static stability. The squared-fan tail provides the highest aerodynamic efficiency while maintaining a high longitudinal stability of the vehicle. In conclusion, this paper provides an innovative study of improving longitudinal stability and aerodynamics through the implementation of bioinspired horizontal stabilizers in vehicles with these characteristics.